1979
DOI: 10.1103/physrevlett.43.1303
|View full text |Cite
|
Sign up to set email alerts
|

Angular Momentum Transfer in Incomplete-Fusion Reactions

Abstract: log resonances and in the fission process.We thank H. Paetz gen<, Schieck for his permanent help in running the Universitat Koln polarized ion source even if only for an unpolarized beam.The measured correlation of charged-particle energies and angles with y-ray multiplicities indicate that the average angular momentum transferred in the capture of 4 He, 8 Be, and 12 C from 153-MeV 16 0 projectiles by a 154 Sm target increases linearly with captured mass. These incomplete-fusion processes are shown to originat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(32 citation statements)
references
References 9 publications
1
30
1
Order By: Relevance
“…Some early e orts were made along this line 15,17] but the reactions involved beams and energies that would be of little interest to spectroscopists. It would also be interesting to investigate reactions involving other weakly bound stable beams, such as 9 Be and 11 B.…”
Section: Discussionmentioning
confidence: 99%
“…Some early e orts were made along this line 15,17] but the reactions involved beams and energies that would be of little interest to spectroscopists. It would also be interesting to investigate reactions involving other weakly bound stable beams, such as 9 Be and 11 B.…”
Section: Discussionmentioning
confidence: 99%
“…Wilczynski et al [17], established ICF as a natural extension of CF for higher ℓ-values (above ℓ crit ) associated with peripheral interactions. The non-central nature of ICF has also been emphasized by Geoffroy et al [18], Trautmann et al [19], and Inamura et al [20]. In the most widely used breakup fusion (BF) -model [21] of Udagawa and Tamura, the projectile is assumed to break-up into constituent α-clusters (e.g., 16 O may break-up into 12 C+α and/or 8 Be+ 8 Be) within the nuclear field of the target nucleus.…”
Section: Introductionmentioning
confidence: 87%
“…induced reactions on heavy nuclei was performed to investigate CF-ICF using particle-gamma coincidence techniques and recoil range distribution techniques [11][12][13][14][15][20][21][22][23]. It is observed that the articles [18][19][20][21] are consistent with the sum rule model [24] and [13][14][15]23] with the breakup fusion model [25] [18,19,[26][27][28]. The dependence of the localization of the entrance channel angular momentum (l) window on deformation of target nucleus was well described in the review of Gerschel et al [29].…”
Section: Introductionmentioning
confidence: 99%